Religious Participation of Millennial Muslim Women: A Sociological Study of the Influence of Interaction and Motivation to Use Social Media - Chaerani, Annisa Nurul; Utami, Ririn Rizkiya; Aly, Kamall; Alwi, Muammar; Y, Ansari (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study analyzes how interaction and motivation to use social media influence religious participation, especially among millennial Muslim women. Social media has become a new public space for religious people to interact, share, and organize religious activities. This study uses a quantitative method by distributing online questionnaires to millennial generation Muslim women who follow @kingfasialjim Instagram account. Researchers chose to take samples with purposive sampling using Malhotra's technique and obtained a sample of 100 people. The results showed that social media interaction has a significant influence on religious participation, while motivation to use social media has no significant influence when analyzed individually. However, when interaction and motivation were analyzed together, both were found to have a significant influence on religious participation. The findings are relevant for religious communities and stakeholders who want to understand the dynamics of religious expression and participation in the social media era.